Modelling the Growth of Ferrous Metallurgy Literature: a Study Based on Iron Making and Steelmaking - Ramakrishna, N. V. (Journal of Information and Knowledge, 2014)
This paper examines the growth of references over the past fifteen years (1994-2008) and attempt to identify the appropriate growth models from the several competing growth models. It was found that the linear model of growth provide better fits to observed data, whereas the exponential model, a popular model of literature growth, provided the poorest fit. The R2 values were used to determine which model performed best.